Pengembangan Culture, Self, and Personality Dalam Diri Manusia - Antonius Atosökhi Gea (Humaniora, 2010)
People have different perception about themselves, especially in the case of they are independent or interdependent people in their life. The article discussed the different of self concept related to cultural differences, especially between individual and collective cultures. The different concept on “self” brings a big influence on cognitive development, motivation, and emotion. On the other hand, culture also has impacts on human behavior development, especially those related to locus of control and self esteem. Both individual and collective cultures have some impacts on to what extend a person can be a supervisor towards his own behavior. Locus of control can be available either in internal or external of a person. Collective culture is more supportive in achieving global self esteem, while individual culture more tends to achieve self competence, another aspect of self esteem. Related to the determination of the five-factor model personality that has been acknowledged as the basic of basic human personality, it can be concluded that culture, self, and personality can be built from human internal, combined by some inputs of his environment which play important role to activate those mechanism.